Recent Trends of Polymer Mediated Liposomal Gene Delivery System. (27th August 2014) - Kundu, Shyamal Kumar; Sharma, Ashish Ranjan; Lee, Sang-Soo; Sharma, Garima; George Priya Doss, C.; Yagihara, Shin; Kim, Do-Young; Nam, Ju-Suk; Chakraborty, Chiranjib
Abstract : Advancement in the gene delivery system have resulted in clinical successes in gene therapy for patients with several genetic diseases, such as immunodeficiency diseases, X-linked adrenoleukodystrophy (X-ALD) blindness, thalassemia, and many more. Among various delivery systems, liposomal mediated gene delivery route is offering great promises for gene therapy. This review is an attempt to depict a portrait about the polymer based liposomal gene delivery systems and their future applications. Herein, we have discussed in detail the characteristics of liposome, importance of polymer for liposome formulation, gene delivery, and future direction of liposome based gene delivery as a whole.